Clinical Presentation and Management of Inguinoscrotal Swelling in Children - Mahanta, Kinkar; Brahma, Rocket Chandra; Doley, Satya Bikash; Patgiri, Lakhyajyoti; Sarkar, Rosidul; Sakachep, Papu (Journal of Neonatal Surgery, 2025)
BACKGROUND: One of the most frequent categories of diseases observed in clinical surgical practice is inguinoscrotal disease. The Pathognomic clinical features are infrequently present in patients; hence the diagnostic problem is difficult in these cases. The commonest cause of inguinoscrotal swelling in children is persistent processes vaginalis. Males are affected 3-6 times more than females. According to their morphology and vascularity, investigations like colour doppler ultrasonography with a high-frequency transducer can assist characterise intra-scrotal swellings. So, it is possible to distinguish between swellings that need immediate surgery and those that may be treated conservatively. METHOD: We retrospectively reviewed hospital register records of 100 patients who underwent operative procedure for inguinoscrotal swelling conducted in the department of paediatric surgery at Assam Medical College & Hospital for a period of 2 years from June 2021 to May 2023. RESULTS: A total of 100 cases were selected of which 61 cases were diagnosed as inguinal hernia, 23cases were hydrocele, 9 cases of undescended testis, 4 cases of communicating hydrocele with hernia and 3 cases of encysted hydrocele of chord. Age group of 0-1 year has the highest number of cases of inguinal hernia (21.3%). 10 cases and 9 cases presented in the age groups 4-5 years and 1-2 years respectively. The treatment consists of operative intervention in all the 100 cases of inguinoscrotal swelling, out of which herniotomy (64%) was the most common procedure performed followed by ligation of sac in cases of hydrocele. CONCLUSION: Inguinal hernias and hydroceles in children continue to be the most prevalent congenital defects seen by surgeons. The key to preventing complications with an inguinal hernia is early identification and treatment